Decoding the Luxury Brand Attachment: The Power of Social Media in Driving Consumer Action in Kuwait - Marsela Thanasi-Boçe; Syed Faizan Hussain Zaidi; Selma Kurtishi-Kastrati; Mujtaba Momin (Human Behavior and Emerging Technologies)
Enhancing the capacity of a luxury brand to stir a deep connection with customers has always been the focus of practitioners in the luxury industry. This study explores the potential role of social media in converting attachment with a luxury brand into desirable marketing outcomes. The relationships between “luxury brand attachment,” “motivation,” “social media usage,” “word-of-mouth,” and “purchase intention” are examined to understand the drivers and outcomes of luxury brand attachment in social media. A questionnaire was administered to a sample of 341 social media users on various platforms. Data were analyzed using SPSS and Amos. The results revealed that the most important attribute generating luxury attachment in social media is the capacity of a luxury brand to show prestige and status. The direct relationship between luxury brand attachment and purchase intentions is nonsignificant. A stronger attachment to a luxury brand does not entice direct intention to purchase it unless certain motives drive consumers’ luxury engagement in social media. These insights can guide marketing managers in creating effective strategies for their luxury products.